PROGRAM KEMITRAAN SATUAN PAUD DENGAN KELUARGA DI PAUD AL FIKRI PONTIANAK UTARA - Sumaryati, Desi; Halida, Halida; Yuniarni, Desni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to describe the partnership program of early childhood education units (PAUD) with families in Al Fikri PAUD North Pontianak. This study uses descriptive methods and uses a qualitative approach. The data source of this study is the head of PAUD, teachers, and parents of Al Fikri PAUD students, the data comes from the results of interviews, observations, and documentation. The results of the research program of partnership programs for early childhood education (PAUD) units with families showing, the partnership program plan is carried out in two stages, namely the needs analysis stage and the preparation phase of the partnership program action plan. The partnership program is carried out through several activities, namely capacity building for PAUD residents, meetings of class teachers and parents, parent classes, parental involvement as motivators / inspirers for students, involvement of parents in class, and year-end performances. Barriers that occur because of the time factor that makes parents unable to attend program activities and the attitude of parents who are less cooperative. Evaluation is carried out with two types of evaluation, namely family evaluation and program evaluation.Â Keywords: Partnership Program, Family